Correlation between chemical properties and electronic structure of pseudomorphic Cu monolayers on Ni(1 1 1) and Ru(0 0 0 1) - Koschel, Herbert; Birkenheuer, U.; Held, Georg; Steinrück, Hans-Peter (Surface Science, 2001)
The adsorption of CO and benzene on pseudomorphic Cu monolayers on Ni(111) and Ru(0001) shows pronounced differences: For Cu/Ni(111) a behavior very similar to that of Cu(111) is observed, for Cu/Ru(0001) the adsorbate substrate bond is significantly strengthened for both molecules, as is deduced from a shift of the desorption temperature to higher values. Based on angle resolved UV photoelectron spectroscopy using synchrotron radiation at BESSY and density functional calculations we have determined the two-dimensional band structure of the pseudomorphic Cu monolayers on Ni(111) and Ru(0001). Our results show that for Cu/Ni(111) only weak coupling of the Cu3d states to the Ni substrate states occurs. On the other hand, strong coupling is observed for Cu/Ru(0001). This difference is made responsible for the strongly modified chemical properties of Cu/Ru(0001) as compared to Cu/Ni(111). © 2001 Elsevier Science B.V.